2015
DOI: 10.4141/cjas-2014-131
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding strategically blended feed pellets on rumen fermentation and nutrient digestion

Abstract: . 2015. Effect of feeding strategically blended feed pellets on rumen fermentation and nutrient digestion. Can. J. Anim. Sci. 95: 243Á254. Five rumen-cannulated heifers (631931 kg) were used in a 5 )5 Latin square design to evaluate the effect of feeding blended by-product feed pellets (BP) on rumen fermentation and nutrient utilization. Four BP were formulated to be high in starch (HS) or fat (HF) and either low (LSP) or high (HSP) in soluble crude protein. The control diet consisted of 49.1% forage and 50.9%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
2
2
0
Order By: Relevance
“…Similar to the findings of Yoo et al [ 10 ], our study showed no significant difference in NH 3 -N concentration between the groups fed with Corn TMR (7.12 mg/dL) and Rice TMR (7.33 mg/dL). Moreover, the ruminal NH 3 -N concentration in our study fell within the previously suggested optimal range for proper rumen fermentation (3.3 to 8.5 mg/dL) [ 23 ]. Regarding the VFA composition, the proportion of butyrate was higher in the Rice TMR group than in the Corn TMR group.…”
Section: Discussionsupporting
confidence: 83%
“…Similar to the findings of Yoo et al [ 10 ], our study showed no significant difference in NH 3 -N concentration between the groups fed with Corn TMR (7.12 mg/dL) and Rice TMR (7.33 mg/dL). Moreover, the ruminal NH 3 -N concentration in our study fell within the previously suggested optimal range for proper rumen fermentation (3.3 to 8.5 mg/dL) [ 23 ]. Regarding the VFA composition, the proportion of butyrate was higher in the Rice TMR group than in the Corn TMR group.…”
Section: Discussionsupporting
confidence: 83%
“…Oh et al [ 38 ] reported that the rumen NH 3 -N concentration of fattening Hanwoo steer was in the range of approximately 4–15 mg/dL immediately after feeding. Ruminal NH 3 -N in the current study was within the range (3.3 to 8.5 mg/dL) previously reported as optimum for rumen fermentation [ 39 ]. There was no significant difference in VFA production between dietary groups (CON: 65.7 mM; GINSENG: 66.1 mM).…”
Section: Discussionsupporting
confidence: 82%
“…Spiehs and Varel (2009) reported similarly high N retention values ranging from 59.4 to 72.6 g d -1 when corn distillers by-products were fed to beef cattle. As well, Walter et al (2012) and Zenobi et al (2015) reported higher than expected N retention values when high protein feeds, such as DDGS or by-productbased pellets, were fed to growing and finishing cattle. The higher than expected N retention could be due to issues with experimental protocol such as N loss during drying of fecal samples or from urine samples.…”
Section: Nitrogen Balancementioning
confidence: 81%
“…On d 19, rumen fluid was collected every 2 h over 24 h. Days 21-24 were used for measurement of rumen pH using in-dwelling pH probes. From d 24 to the end of each period, cattle were fed at 95% of voluntary intake to assure consumption of all feed (Zenobi et al 2015). On d 26, urinary catheters were inserted, and total urine and fecal collections were carried out from d 27 to d 32.…”
Section: Experimental Designmentioning
confidence: 99%